Identification of in planta bioprotectants against Fusarium wilt in Medicago sativa L. (lucerne) from a collection of bacterial isolates derived from Medicago seeds - Herath Dissanayakalage, Shenali Subodha; Kaur, Jatinder; Achari, Saidi R.; Sawbridge, Timothy I. (Frontiers in Microbiology, 2025)
Fusarium wilt caused by Fusarium oxysporum f. sp. medicaginis (Fom) is an important disease affecting lucerne/alfalfa cultivations worldwide. Medicago sativa L. (lucerne) is one of the major legume crops in global forage industry. This study aimed to identify bacteria capable of biologically controlling the wilt pathogen through a comprehensive screening of bacterial isolates obtained from domesticated and wild growing Medicago seeds. Using a multi-tiered evaluation pipeline, including in vitro, soil-free and potting mix-based pathogenicity and bioprotection assay systems, the bioprotection efficacy of 34 bacterial isolates derived from Medicago seeds was initially evaluated against six Fusarium strains in vitro. Fusarium oxysporum (Fo) F5189, which has previously been characterized as a Fusarium oxysporum f. sp. medicaginis isolate causing Fusarium wilt in lucerne was selected for in planta assays. Lucerne cultivars Grazer and Sequel, representing susceptible and resistant genotypes were chosen to assess the disease progression. Pathogenicity and bioprotection time-course studies were conducted to understand the temporal dynamics of host-pathogen interactions and efficacy of the bioprotectants. The disease symptoms were scored using a disease rating index developed in this study. The results indicated variability in bioprotection efficacy across bacterial isolates, with some strains suppressing disease in both soil-free and potting mix-based systems. Paenibacillus sp. (Lu_MgY_007; NCBI: PQ756884) and Pseudomonas sp. (Lu_LA164_018; NCBI: PQ756887) were identified as promising bioprotectants against Fusarium wilt under tested growth conditions. The time-course studies highlighted the critical role of persistent biocontrol activity and precise timing of biocontrol application for achieving long-term disease suppression. Overall, the observed reduction in disease severity underscores the potential of these bioprotectants as sustainable strategies for managing Fusarium wilt in lucerne cultivars. However, comprehensive molecular-level analyses are warranted to elucidate the underlying pathogenicity and bioprotection mechanisms, offering valuable insights for the development of more precise and effective future biocontrol strategies in agricultural systems.